Marriage migration: Lived experience of foreign spouses married to Malaysian citizens - Tedong, Peter Aning; Roslan, Kazimah; Kadir, Abdul Rahim Abdul (Universiti Putra Malaysia, 2018)
Marriage migration has led to marriage migrants as a significant aspect of migration. While much of the literature on migration in the Malaysian context discusses labour migration, very little is documented on marriage migration in Malaysia, especially concerning foreign spouses’ viewpoint on their international marriage. Therefore, this paper sought to investigate and document the foreign spouses’ lived experience in several aspects of life from acquiring the spouse visa to employment to family and relationship with friends in Malaysia. Results obtained from data collected through in-depth interviews give the overview that foreign spouses experience difficulties due to their status as a ‘foreigner’. Foreign spouses’ experience of living in Malaysia is related to the idea that a ‘foreigner’ is considered socially excluded in the country, leading to difficulties. Overall, foreign spouses face many challenges living in Malaysia.